Negative pressure wound therapy: mechanisms of action and clinical uses - Orgill, Dennis P. (Henry Stewart Talks, 2014)
History and Technology Transfer, Biology of Stretching Skin, Primary Mechanisms of NPWT: Macrodeformation, Microdeformation, Fluid removal, Moist wound environment, Secondary Mechanisms: Angiogenesis, Inflammation, MMPs, Peripheral Nerves, Case examples: Sternal wounds, Open Abdomen, Groin Wounds, Skin Grafts